1989
DOI: 10.1002/jat.2550090106
|View full text |Cite
|
Sign up to set email alerts
|

Tumours of the respiratory tract in rats and hamsters following chronic inhalation of engine exhaust emissions

Abstract: The potential carcinogenic effect of inhaled automobile exhaust emissions was examined in rodents. Both rats and hamsters were exposed to the emissions from (1) a gasoline engine, (2) a gasoline engine fitted with a three-way catalytic converter, (3) a diesel engine and (4) a diesel engine with particle filtration. Exposures were for 16 hours per day, 5 days per week, for 2 years. All hamsters were sacrificed at the end of the 2-year exposure period, whereas the rats surviving after 2 years of exposure were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 9 publications
2
39
0
1
Order By: Relevance
“…Both of them are the result of incomplete combustion of the fiiel or lubricating oil. Some recent laboratory research on rats has shown that the solid carbon, or soot, portion of diesel particulates is probably essential for initiation of tumor formation [2,3]. The associated soluble organic fraction, particularly the polynuclear aromatic hydrocarbons (PAH) and Nitro-PAH, also makes a contribution to the overall carcinogenic efiect [4].…”
Section: Introductionmentioning
confidence: 99%
“…Both of them are the result of incomplete combustion of the fiiel or lubricating oil. Some recent laboratory research on rats has shown that the solid carbon, or soot, portion of diesel particulates is probably essential for initiation of tumor formation [2,3]. The associated soluble organic fraction, particularly the polynuclear aromatic hydrocarbons (PAH) and Nitro-PAH, also makes a contribution to the overall carcinogenic efiect [4].…”
Section: Introductionmentioning
confidence: 99%
“…Using these criteria, we identified eight chronic inhalation studies (16,(33)(34)(35)(36)(37)(38)(39). Some studies indude results from animals sacrificed at interim periods (36,37).…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…Some studies indude results from animals sacrificed at interim periods (36,37). The exposure concentrations and study results are summarized in Table 1, and Figure 1 illustrates data on the proportion of animals (males and females combined) with a lung tumor as a function of exposure to DEP, using the metric described below.…”
Section: Methodology and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cancer study by Brightwell et al (9) of rats and hamsters exposed to GE, mentioned above, also included limited evaluations of respiratory function (24), but no significant alterations were observed. In 1966, Hueter et al (25) reported limited measurements of the respiratory function of guinea pigs during 20 months of exposure to GE at 100 ppm CO, but found no significant effects.…”
Section: Lung Cancer From Engine Exhaustmentioning
confidence: 99%